PEMBELAJARAN MATERI PENYAJIAN DATA PADA SISWA SMP KELAS VII DENGAN MENGGUNAKAN PROBLEM BASED LEARNING BERBANTUAN MICROSOFT EXCEL - Lilis Saleha; Eka Senjayawati (IKIP Siliwangi, 2022)
This observe aims to decide the effects of college students' solutions to the information presentation material. Mastery of data presentation material is one of the activities in making reviews on studies results which have been carried out so that they can be understood and analyzed according with the preferred objectives. The statistics presented have to be simple and clear so that it is straightforward to study. The presentation of records is supposed so that observations can without difficulty apprehend what is presented for making assessments, comparisons and others. This study aims to present a data using a problem based learning assisted by Microsoft Excel. This research method uses descriptive qualitative method. The population in this study were seventh grade junior high school students involving a sample of 30 students. Data collection was obtained by documenting the results of student tests based on instrument questions on the presentation of data containing indicators of competency achievement. The results obtained by students with an overall total score who can solve the problem of presenting data calculated using Microsoft Excel based on percentage (%) get 81% which includes the interpretation which is moderate.